The influence of stakeholder perspectives on the end-of-life allocation in the life cycle assessment of lithium-ion batteries - Husmann, Jana; Ali, Abdur-Rahman; Cerdas, Felipe; Herrmann, Christoph (Frontiers in Sustainability, 2023)
With an increasing number of electric vehicles on the roads, recycling is an important topic to design circular supply chains for batteries. To stimulate such circular supply chains, the new EU battery directive includes mandatory recycled content in the batteries and recovery rates of materials for lithium-ion batteries on the European market. Modelling the End of Life of batteries as part of a life cycle assessment (LCA) is methodological challenging as batteries are quite complex product systems. One of these challenges is the allocation of material impacts from the different life cycle stages along subsequent product life cycles. We analysed the different stakeholders in the life cycle of a lithium-ion battery and identified possible LCA questions based on their decision contexts. For each LCA question, an LCA archetype was defined that includes the functional unit, the system boundary and the allocation procedure. These archetypes are applied and tested in a case study. The results show a significant variance depending on the archetype used. This highlights the importance of understanding the stakeholder perspective in LCA and decision support.